Inflammasomes and Fibrosis - Zhang, Wen-Juan; Chen, Shu-Juan; Zhou, Shun-Chang; Wu, Su-Zhen; Wang, Hui (Frontiers in Immunology, 2021)
Fibrosis is the final common pathway of inflammatory diseases in various organs. The inflammasomes play an important role in the progression of fibrosis as innate immune receptors. There are four main members of the inflammasomes, such as NOD-like receptor protein 1 (NLRP1), NOD-like receptor protein 3 (NLRP3), NOD-like receptor C4 (NLRC4), and absent in melanoma 2 (AIM2), among which NLRP3 inflammasome is the most studied. NLRP3 inflammasome is typically composed of NLRP3, ASC and pro-caspase-1. The activation of inflammasome involves both “classical” and “non-classical” pathways and the former pathway is better understood. The “classical” activation pathway of inflammasome is that the backbone protein is activated by endogenous/exogenous stimulation, leading to inflammasome assembly. After the formation of “classic” inflammasome, pro-caspase-1 could self-activate. Caspase-1 cleaves cytokine precursors into mature cytokines, which are secreted extracellularly. At present, the “non-classical” activation pathway of inflammasome has not formed a unified model for activation process. This article reviews the role of NLRP1, NLRP3, NLRC4, AIM2 inflammasome, Caspase-1, IL-1β, IL-18 and IL-33 in the fibrogenesis.